Evaluating the design of the Integrated Care for Older People: a theory of change approach - Gutiérrez-Barreto, Samuel E.; Sosa-Tinoco, Eduardo; Rojas-Calixto, Oscar; Deniss-Navarro, Zayda; Avila-Avila, Arturo; Gutierrez, Juan Pablo (Frontiers in Medicine, 2023)
Introduction: Given the progressive aging of the population, there is an urgent need at the health systems level to implement effective models to care for older people (OP). Healthy aging is imperative to reach Sustainable Development Goals. The World Health Organization (WHO) developed the Integrated Care for Older People (ICOPE) strategy to address this challenge. Implementing ICOPE requires its adaption to a specific context. We propose a pathway for such adaptation through an evaluation of the design of ICOPE; thus, we aim to describe the Theory of Change (ToC) of ICOPE and evaluate it for its implementation in Mexico City. Methods: Based on the WHO and published literature documentation, we drafted an initial ToC for ICOPE. Then, we validated the ToC with experts in ICOPE then evaluated and refined it by discussing the causal pathway, intervention required to activate it, rationale, and assumptions in consecutive workshops with 91 stakeholders and healthcare workers, using the nominal group technique to reach a consensus. Results: The resulting ToC has the potential to contribute to healthy aging by three expected impacts: 1) Prevent, reverse, or delay the decline of IC in OP, 2) Improve the quality of life of OP, and 3) Increase disability-free life expectancy. The ICOPE causal pathway had ten preconditions, including the availability of resources, identifying at-risk individuals, available treatments, and evaluating results. Discussion: We adapted ICOPE to a specific implementation context by evaluating its ToC in a participatory process that allows us to identify challenges and address them, at least in terms of the guidelines to operate the strategy. As ICOPE is an approach for a primary healthcare system, its adoption in a community healthcare program is promising and feasible. Evaluation as a tool could contribute to the design of effective interventions. The evaluation of the design of ICOPE for its implementation contributes to the strength of its potential to improve care for OP. This design for implementing ICOPE has the potential to scale in similar contexts, for example, in other lower-middle-income countries.